Genetic Diversity of Bubalus bubalis in Germany and Global Relations of Its Genetic Background - Noce, Antonia; Qanbari, Saber; González-Prendes, Rayner; Brenmoehl, Julia; Luigi-Sierra, María Gracia; Theerkorn, Michael; Fiege, Marc-André; Pilz, Heike; Bota, Adrian; Vidu, Livia; Horwath, Csaba; Haraszthy, László; et al. (Frontiers in Genetics, 2021)
This is the first study to explore the genetic diversity and population structure of domestic water buffalo (Bubalus bubalis) in Germany and their potential relations to herds in other parts of Europe or worldwide. To this end, animals from different herds in Germany, Bulgaria, Romania, and Hungary were genotyped and compared to genotypes from other populations with worldwide distribution and open to the public. The pilot study analyzed population structure, phylogenetic tree, and inbreeding events in our samples. In buffalos from Germany, a mixed genetic make-up with contributions from Bulgaria (Murrah breed), Romania, and Italy was found. All in all, a high degree of genetic diversity was identified in European buffalos, and a novel genotype was described in Hungarian buffalos by this study. We demonstrate, that European buffalos stand out from other buffalo populations worldwide, supporting the idea that buffalos not completely disappeared from the European continent during the late Pleistocene. The high genetic diversity in European buffalos seems to be an excellent prerequisite for the establishment of local breeds characterized by unique traits and features. This study may also be considered as an initial step on the way to genome characterization for the sustainable development of the buffalo economy in Germany and other parts of Europe in the future.